Distinct mRNA expression profiles and miRNA regulators of the PI3K/AKT/mTOR pathway in breast cancer: insights into tumor progression and therapeutic targets - Sirek, Tomasz; Król-Jatręga, Katarzyna; Borawski, Przemysław; Zmarzły, Nikola; Boroń, Dariusz; Ossowski, Piotr; Nowotny-Czupryna, Olga; Boroń, Kacper; Janiszewska-Bil, Dominika; Mitka-Krysiak, Elżbieta; Grabarek, Beniamin Oskar (Frontiers in Oncology, 2025)
BackgroundBreast cancer remains a leading cause of mortality among women, driven by the molecular complexity of its various subtypes. This study aimed to investigate the differential expression of genes and miRNAs involved in the PI3K/AKT/mTOR signaling pathway, a critical regulator of cancer progression.MethodsWe analyzed tumor tissues from five breast cancer subtypes—luminal A, luminal B HER2-negative, luminal B HER2-positive, HER2-positive, and triple-negative breast cancer (TNBC)—and compared them with non-cancerous tissues. Microarray and qRT-PCR techniques were employed to profile mRNAs and miRNAs, while bioinformatic tools predicted miRNA-mRNA interactions. Statistical analysis was performed with a statistical significance threshold (p) < 0.05.ResultsWe identified several upregulated genes across all subtypes, with TNBC and HER2-positive cancers showing the most significant changes. Key genes such as COL1A1, COL4A1, PIK3CA, PIK3R1, and mTOR were found to be overexpressed, correlating with increased cancer aggressiveness. miRNA analysis revealed that miR-190a-3p, miR-4729, and miR-19a-3p potentially regulate these genes, influencing the PI3K/AKT/mTOR pathway. For instance, reduced expression of miR-190a-3p may contribute to the overexpression of PIK3CA and other pathway components, enhancing metastatic potential.ConclusionOur findings suggest that the PI3K/AKT/mTOR pathway and its miRNA regulators play crucial roles in breast cancer progression, particularly in aggressive subtypes like TNBC. The identified miRNAs and mRNAs hold potential as biomarkers for diagnosis and treatment, but further validation in functional studies is required. This study provides a foundation for targeted therapies aimed at modulating this critical pathway to improve breast cancer outcomes.